Effect of Salicylic Acid and Drought Stress on Germination and Activity of Antioxidant Enzymes of Barely - M. Sharafizadeh (علوم و فناوری بذر ایران)
In order to study effectpretreatment salicylic acid under drought stress on germination characteristics this research was conducted in May 1393. Barley seed varieties Zahak after soaking in solution [zero (water) 0.7 1.2 and 2.7 mM ) of salicylic acid (SA) for 24 hours under conditions of drought stress on the germination dishes. Containing 10 ml of a solution of polyethylene glycol (6000) with potentials [zero (control), -0.5 MPa, 1 MPa and 1.5 MPa] moved, and related traits were determined germination. The results showed that the maximum effect of salicylic acid on germination time, reduce stress levels were low. The highest germination percentage (93 %) and the effective yield of seed soaking with the minimum concentration of salicylic acid 0. 7 mM ) and low levels of stress were gained. Vigor and Seedling vigor index at high concentrations of salicylic acid and high levels of stress decreased. In this study, drought stress reduced the germination traits and salicylic acid reduces the adverse effect of drought stress on germination was related traits.